2019
DOI: 10.2196/14602
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Randomized Controlled Trial of a Web-Based Growth Mindset Intervention to Enhance the Effectiveness of a Smartphone App for Smoking Cessation

Abstract: Background Although smartphone apps have shown promise for smoking cessation, there is a need to enhance their low engagement rates. This study evaluated the application of the growth mindset theory, which has demonstrated the potential to improve persistence in behavior change in other domains, as a means to improve engagement and cessation. Objective This study aimed to explore the feasibility, utility, and efficacy of a Web-based growth mindset intervention for addic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Only 5% of smokers who want to quit smoking access a smoking cessation service each year. Nevertheless, the drop out is still higher [5]. There were some evidences found that using mobile and web-based intervention can promote smoking cessation.…”
Section: Introductionmentioning
confidence: 98%
“…Only 5% of smokers who want to quit smoking access a smoking cessation service each year. Nevertheless, the drop out is still higher [5]. There were some evidences found that using mobile and web-based intervention can promote smoking cessation.…”
Section: Introductionmentioning
confidence: 98%
“…Of the various smartphone uses, the role of smartphone use for entertainment on mental health is controversial [ 10 ]. Unlike some other smartphone use behaviors that contribute to problem solving (e.g., using a smartphone to ask for help or gather useful information) [ 27 , 28 ], using a smartphone for entertainment, while distracting from a negative event or situation in the short term [ 29 ], may not be beneficial to mental health in the long term [ 30 ]. In various theoretical models, the use of ICT for entertainment has been identified as an antecedent of problematic technology use (e.g., problematic smartphone use, PSU) [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been little assessment of the quality of content, engagement and reach of apps that are underpinned by research or theory, compared with apps commonly used in the marketplace [46,[59][60][61][62][63][64][65][66][67][68][69] that purport to assist smokers with mental health issues to quit [71,72].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that smoking cessation apps can engage smokers with mental health issues, [28] including those who are not already receiving nor seeking professional help [68], and may promote smoking cessation or reduction of tobacco consumption [69], and improve mental health status [46]. With the proliferation of smartphones, mobile health tools are uniquely positioned to reach and in uence the smoking populations that need both smoking cessation and mental health support [70].However, there has been little assessment of the quality of content, engagement and reach of apps that are underpinned by research or theory, compared with apps commonly used in the marketplace [46,[59][60][61][62][63][64][65][66][67][68][69] that purport to assist smokers with mental health issues to quit [71,72].…”
mentioning
confidence: 99%